(untitled) (World Science, 2020)
The article reveals the relevance and essence of the metabolic syndrome problem. According to studies, in developed countries 15-25% of people aged 40-70 years have symptoms of metabolic syndrome. The role of a nurse in the effective prevention and treatment of metabolic syndrome is presented. An improvement in the well-being and quality of life of patients with metabolic syndrome after correction of the patient’s lifestyle was noted.